Pretreatment methods of organic wastes for biogas production - Salihu, Aliyu; Alam, Md Zahangir (Science Alert, 2016)
During biogas production, the rate-determining step for the conversion of complex organic matter is the hydrolysis. Different pretreatment methods aid in facilitating the anaerobic digestion by increasing the rate of organic matter hydrolysis. This in effect results in enhanced production of biogas and aids in waste stabilization as well as disposal. This review gives an overview of the methods used in pretreating organic wastes including mechanical, thermal, chemical and biological. In addition, hybrid method (physico-chemical) involving more than one technology has been useful in enhancing waste solubilization and anaerobic digestion. Thus, economic analysis including the cost of operation and the benefits derived in form of biogas, waste minimization and treatment should be considered during the selection of any pretreatment methods for large scale application.